Antitumoral and Anti-inflammatory Roles of Somatostatin and Its Analogs in Hepatocellular Carcinoma. (27th November 2021) - Periferakis, Argyrios; Tsigas, Georgios; Periferakis, Aristodemos-Theodoros; Badarau, Ioana Anca; Scheau, Andreea-Elena; Tampa, Mircea; Georgescu, Simona Roxana; Didilescu, Andreea Cristiana; Scheau, Cristian; Caruntu, Constantin
Abstract : Hepatocellular carcinoma (HCC) is the most common primary liver cancer and affects about 8% of cirrhotic patients, with a recurrence rate of over 50%. There are numerous therapies available for the treatment of HCC, depending on cancer staging and condition of the patient. The complexity of the treatment is also justified by the unique pathogenesis of HCC that involves intricate processes such as chronic inflammation, fibrosis, and multiple molecular carcinogenesis events. During the last three decades, multiple in vivo and in vitro experiments have used somatostatin and its analogs (SSAs) to reduce the proliferative and metastatic potential of hepatoma cells by inducing their apoptosis and reducing angiogenesis and the inflammatory component of HCC. Most experiments have proven successful, revealing several different pathways and mechanisms corresponding to the aforementioned functions. Moreover, a correlation between specific effects and expression of somatostatin receptors (SSTRs) was observed in the studied cells. Clinical trials have tested either somatostatin or an analog, alone or in combination with other drugs, to explore the potential effects on HCC patients, in various stages of the disease. While the majority of these clinical trials exhibited minor to moderate success, some other studies were inconclusive or even reported negative outcomes. A complete evaluation of the efficacy of somatostatin and SSAs is still the matter of intense debate, and, if deemed useful, these substances may play a beneficial role in the management of HCC patients.